(untitled) (Journal of Applied Learning and Teaching, 2023)
This paper explores the reciprocal relationship between thinking and writing skills using task-based language teaching. The tasks designed for a second language writing classroom must activate learners’ working memory and provide scope for thinking and content generation. If the learners find the task to be more relevant, interesting and related to their experience, they automatically get oriented towards the task with a pleasant affective mindset. In this regard, writing tasks as a pedagogical tool and method have been employed to develop the thinking and cohesive writing of the students. The participants of this experimental study are the postgraduate students of National Institute of Technology (NIT)-Tiruchirappalli, India. The structured writing tasks have been administered in different discourse types to the students in a span of one and a half months. The delayed post task has been administered to test the sustenance level of their writing proficiency developed through the course. The findings of the study reveal that there is a significant correlation between task variables, students’ thinking and writing skills. The results indicate that students’ thinking skills have been empowered to develop the central idea logically and cohesively through an integrated writing task. The study recommends that researchers design writing tasks in which the students will be able to relate to their real-life situations, and in turn, content generation will become congenial for students to process in their cognitive domain.